Does the integration of response services lead to meaningful change in healthcare activity? A case study evaluation. Issue 3 (20th June 2019) - Hinde, Sebastian; Setters, Jo; Bojke, Laura; Hex, Nick; Richardson, Gerry
Abstract : Purpose: The aim of the NHS England Vanguards of new care models was to improve healthcare provision and integration through the coordination of services, seeking to deliver the Five Year Forward View . The purpose of this paper is to report on an extensive analysis of one of the Vanguard programmes, exploring whether the implemented integrated response service (IRS) based in Harrogate, England, resulted in any meaningful change in secondary healthcare activity. Design/methodology/approach: The authors used an interrupted time series framework applied to aggregate secondary care data, specifically emergency attendances for patients 65+, emergency bed days for all adults and non-elective admissions for 65+. Synthetic and geographic comparator data were employed to inform additional scenario analyses. Findings: The majority of the analyses conducted found no statistically significant effect of the IRS team in either direction, suggesting that there was no change in the metrics that could be separated from natural variation. The data correlated with the findings of a qualitative analysis and challenges faced in staffing the team towards the end of the analysis period and the eventual disbanding of the IRS. Research limitations/implications: The analysis was partially hampered by data access challenges, limited to poorly specified aggregate secondary care data, and a poorly specified intervention. Furthermore, the follow-up period was limited by the disbanding of the service. Originality/value: This analysis indicates that the Harrogate-based IRS team is unlikely to have delivered any sustained quantifiable impact on the intended secondary care outcomes. While this does not necessarily demonstrate a failure of the core principle behind the drive for integrated care, it is an important exploration of the challenges of evaluating such a service.